The Effects of Mood Disorders and Dissociative Symptoms on Suicide Attempts - Halil ÖZCAN; Ali Emre ŞEVİK (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: The aim of this study is to examine patients with suicide attempts in respect of mood disorders and dissociative symptoms and to understand the impact of these symptoms on suicide attempts. Method: Seventy participants who were directed to psychiatry outpatient department from the Kastamonu State Hospital crisis intervention unit between January 2009 and January 2010 and who agreed to participate in the study were included. All of the patients were evaluated by psychiatric interview. A detailed sociodemographic and clinical data form was filled for all included patients and present or past history of psychiatric illness were explored. The Mood Disorders Questionnaire (MDQ), Beck Depression Inventory (BDI), Beck Suicide Intention Scale (BSIS), Dissociative Experiences Scale (DES) were applied to all participants. Results: The mean score of DES was 39±21.3, of MDQ 7.5±2.5, of BDI 28±14 and of BSIS 15.3±5.8. Participants who scored higher than 7 in the MDQ had statistically more dissociative experiences than those who scored lower than 7 in MDQ. In addition, participants who scored higher than 5 points in the MDQ had more dissociative experiences than those who scored lower than 5 in the MDQ. Having higher scores on DES, MDQ and BDI was positively correlated with having higher scores on BSIS. Conclusion: The etiologies of suicides are complex. Suicide attempter might often have both mood symptoms and dissociative experiences.